A New Method for the Deposition of Metallic Silver on Porous Ceramic Water Filters - Kathryn N. Jackson; James A. Smith (Journal of Nanotechnology)
A new method of silver application to a porous ceramic water filter used for point-of-use water treatment is developed. We evaluated filter performance for filters manufactured by the conventional method of painting an aqueous suspension of silver nanoparticles onto the filter and filters manufactured with a new method that applies silver nitrate to the clay-water-sawdust mixture prior to pressing and firing the filter. Filters were evaluated using miscible displacement flow-through experiments with pulse and continuous-feed injections of E. coli. Flow characteristics were quantified by tracer experiments using [3H]H2O. Experiments using pulse injections of E. coli showed similar performance in breakthrough curves between the two application methods. Long-term challenge tests performed with a continuous feed of E. coli and growth medium resulted in similar log removal rates, but the removal rate by nanosilver filters decreased over time. Silver nitrate filters provided consistent removal with lower silver levels in the effluent and effective bacterial disinfection. Results from continued use with synthetic groundwater over 4 weeks, with a pulse injection of E. coli at 2 and 4 weeks, support similar conclusions—nanosilver filters perform better initially, but after 4 weeks of use, nanosilver filters suffer larger decreases in performance. Results show that including silver nitrate in the mixing step may effectively reduce costs, improve silver retention in the filter, increase effective lifespan, and maintain effective pathogen removal while also eliminating the risk of exposure to inhalation of silver nanoparticles by workers in developing-world filter production facilities.